Auraticoccus cholistanensis sp. nov., an actinomycete isolated from soil of the Cholistan Desert, and emended description of the genus Auraticoccus. Issue 5 (17th April 2020) - Cheema, Mohsin Tassawar; Ye, Jing-Jing; Li, Fei-Na; Lu, Qin-Pei; Abbas, Muhammad; Sajid, Imran; Huang, Da-Lin; Liu, Shao-Wei; Sun, Cheng-Hang
Abstract : A Gram-stain-positive, aerobic, non-motile and non-spore-forming actinobacterium, designated as F435 T, was isolated from soil sample collected from the Cholistan Desert, Pakistan. The taxonomic position of the strain was established by using a polyphasic taxonomic approach. The cells were coccoid-shaped and found in single or arrangement of pairs. The novel strain grew at 15‒37 °C (optimum, 25‒30 °C), pH 7‒11 (optimum, pH 7–8) and in the presence of 0‒8% (w/v) NaCl (optimum, 0 %). Results of blast analysis based on 16S rRNA gene sequences showed that Auraticoccus monumenti MON 2.2 T was its closest relative with 97.4 % similarity followed by Desertihabitans aurantiacus CPCC 204711 T (95.2 %). In phylogenetic trees, strain F435 T formed a robust cluster with the only member of the genus Auraticoccus . The peptidoglycan isomer present in the cell wall was ll -diaminopimelic acid. The major fatty acid was determined to be anteiso-C15 : 0 . Characteristic polar lipids of the strain were diphosphatidylglycerol, phosphatidylglycerol, phosphoglycolipids and glycolipids. The predominant menaquinone was MK-9(H4 ). The genomic G+C content was calculated as 73.5 mol%. The digital DNA–DNA hybridization (GGDC) and average nucleotide identity (ANI) values between strain F435 T and A. monumenti MON 2.2 T were 24.6 and 81.8 %, respectively. Based on the results of phenotypic, chemotaxonomic, phylogenetic and phylogenomic analyses, strain F435 T represents a novel specie of the genus Auraticoccus, for which the name Auraticoccus cholistanensis sp. nov. is proposed. The type strain is F435 T (=JCM 33648 T =CGMCC 1.17443 T ). The description of the genus Auraticoccus has also been emended.